Bibliographic control of Australian higher degree theses: the future role of the Australian digital theses program - Genoni, Paul; Cowan, Roberta (Australian Library and Information Association, 2003)
Australia makes a substantial investment in the production of higher degrees by thesis. Completed theses form an important body of original research data, and underpin the career of many of the nation's leading researchers. There is evidence, however, that there is inadequate bibliographic control of this material, and that as a consequence important research data may be difficult to locate. This article traces attempts to provide access to bibliographic records of Australian theses, highlights the problems with regard to both accessibility and quality of those records, and suggests that these problems might be addressed by an expanded role for the Australian Digital Theses program